Organic matter isotopes reveal enhanced rainfall activity in Northwestern Mediterranean borderland during warm substages of the last 200 kyr - Pasquier, Virgil (2021)
In this study we use bulk sediment organic matter stable isotopes (δ13Corg and δ15N) to examine the nature and timing of preserved organic matter in borehole PRGL1-4 from Northwestern Mediterranean Sea. This region is known as a transitional zone between the North Atlantic atmospheric circulation and the North African monsoon system. In the Gulf of Lion (SE France), increased inputs of organic matter from sediment-laden rivers occurred during warm substages of the last 200 kyr (MIS 5e, 5c, and 5a; MIS 6d, and 6b). Increased terrestrial organic matter are inferred from organic carbon isotopic composition (δ13Corg), and are interpreted as resulting from enhanced rainfall over the Rhone river catchment area. Such increase in terrestrial organic carbon induced enhancement of the primary productivity leading to the formation of local oxygen minimum zone as demonstrated by ∼3‰ values in δ15N. Comparison with regional paleohydrological records from the northern Mediterranean borderlands reveals the regional character of these pluvial events. Taking advantage of the location of PRGL1-4 borehole, out of Mediterranean cyclogenesis area, we suggest that the pluvial events recorded during warm substages of the last 200 kyr occurred in response to enhanced passage of North Atlantic atmospheric perturbation over the Gulf of Lion catchment area (especially over Rhone river watershed which represent 80% of the GoL catchment area), a scenario possibly similar to that encountered today during negative- NAO like conditions. At a regional scale, our data suggests that high rainfall events over the Gulf of Lion catchement area and the Rhone watershed occurred at the time of North African summer monsoon and the sapropel deposition in the Mediterranean basin, thus highlighting a close coupling between mid- (North Atlantic) and low-latitudes (monsoon) climate systems. Importantly, our geochemical evidence from the Gulf of Lion support an extra-Mediterranean source for the regional pluvial events described in many paleoclimatic records from the northern Mediterrean borderlands during warm substages of the last climate cycles. Consequently, we suggest that this region as a whole could provide, in addition to the river runoff from the North African sector, the necessary conditions for the sapropel deposition.